Media Representation of Indonesian Presidential Candidates in The Jakarta Post: A Corpus-Based Critical Discourse Analysis - Rahmasari, Shafira; Munandar, Aris (Allure Journal, 2025)
Media is said to have a big role in society since it provides the readers with the latest information and simultaneously attains a particular purpose by using specific words to shape an ideology. Therefore, this research attempted to investigate the lemma candidate used in news articles, published by The Jakarta Post in February 2024, using Sketch Engine as the corpus tool to uncover how the media portrays the presidential candidate. Collocation and concordance feature was utilized, and it employed Halliday’s (2004) transitivity analysis to examine how presidential candidates are described and Fairclough’s (1995) Critical Discourse Analysis as the approach to interpreting how the discourse presents such a representation. The result shows that the media portrayed the candidate’s general profile by labelling the candidates and their political agenda, as seen through the nouns and adjectives that modified the lemma candidate and the role of the lemma candidate as an actor in the clause. The candidate is also put as a recipient which exposes the political issue, which was informed by the circumstances, such as political polling and electability surveys. In addition, The Jakarta Post appears to contest presidential candidates by labeling the candidate and reporting the issues.